2015
DOI: 10.1007/s00394-015-0941-y
|View full text |Cite
|
Sign up to set email alerts
|

Examination of iodine status in the German population: an example for methodological pitfalls of the current approach of iodine status assessment

Abstract: Over 30 % of participants in the two German surveys had an estimated iodine intake less than the respective age-group-specific EAR. Our data strongly suggest that even in large surveys, hydration status can considerably interfere with the epidemiological iodine assessment parameter UIC. The present data can serve as an example how to evaluate population-based spot urine data on a 24-h basis, independent of hydration status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 28 publications
(32 reference statements)
1
26
0
Order By: Relevance
“…However, in regions with iodine deficiency, the indication for scintigraphy should be independent of the TSH level as stated by the guidelines for clinical practice for the diagnosis and management of thyroid nodules of the American Association of Clinical Endocrinologists, the Associazione Medici Endocrinologi, and the European Thyroid Association (39). This recommendation takes into account that the prevalence of hyperthyroidism and, thus, a suppressed TSH concentration, in patients with HTNs depends on the iodine supply, which is still suboptimal in several European countries, including Germany (1). Two studies from Germany reported that most HTNs are found in patients with a TSH level within the reference range (32,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in regions with iodine deficiency, the indication for scintigraphy should be independent of the TSH level as stated by the guidelines for clinical practice for the diagnosis and management of thyroid nodules of the American Association of Clinical Endocrinologists, the Associazione Medici Endocrinologi, and the European Thyroid Association (39). This recommendation takes into account that the prevalence of hyperthyroidism and, thus, a suppressed TSH concentration, in patients with HTNs depends on the iodine supply, which is still suboptimal in several European countries, including Germany (1). Two studies from Germany reported that most HTNs are found in patients with a TSH level within the reference range (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of thyroid nodules is high, especially in iodine-deficient countries. Germany is a country with a long history of iodine deficiency; even today, the iodine supply is considered suboptimal (1). In general, the prevalence of thyroid nodules in adults without previously diagnosed thyroid disorders was estimated at up to 59%, with a higher prevalence in the older population (2,3).…”
mentioning
confidence: 99%
“…Even in industrialized nations, I malnutrition is still a widespread problem ( Andersson et al, 2012). For instance, in Germany about 30% of the population does not reach the estimated I requirements ( Johner et al, 2016), in spite of ongoing I prophylaxis measures, e.g. , the use of iodized table salt in households, common in this country since several decades.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Dependent on urine volume, simple iodine concentration measurements can be highly variable. In a very recent paper on iodine status of the German population, 33 it could be clearly shown that despite completely different median iodine concentrations in children and adults (117 vs 62 μg/l, measured in several thousands spot urines), both populations had a very similar median estimated iodine intake (calculated by creatinine scaling) when standardized to body surface area (107 vs 103 μg per day per 1.73 m 2 ). Without the creatinine scaling, which transforms the hydration-dependent concentration measurements to a (hydration-independent) 24-h excretion level, an obviously highly misleading conclusion would have been drawn, namely that in Germany, children are iodine sufficient while adults are mildly or borderline moderate iodine deficient (according to the criteria of the World Health Organization).…”
Section: Discussionmentioning
confidence: 94%